Determinants of employee retention in KPJ Klang Specialist Hospital / Sazila Mat Sarif - Mat Sarif, Sazila (2013)
In order to gain competitive advantage that enable the organization different from their competitor, the organization must also have their own talented and valued employee that will bring benefits to the company. The organization must recruit the talented employees in order to achieve the competitive advantage. But, the most important things that the organization did not realize are about the retention of the employees. Employee turnover not only very costly, but also bring the bad image to the organization. As for KPJ Klang Specialist Hospital, researcher is attracted to identify what are the determinants that make the employees remain in that organization. Even though the hospital is still new, but the employees are loyal to the company. Not only have the new employees that had been recruit, there also had employees that transfer from other branch of KPJ Hospital which have been working with KPJ Hospital more than 10 years. The first research objective is to identify the relationship between extrinsic rewards and the retention of the employee. Second objectives are to identify the relationship between employee empowerment and the retention of the employee. Last objectives are to identify the relationship between job satisfaction and the retention of the employee. The total respondents are 50 respondents that are chosen from Support Services Division. The data were collected through distribution of questionnaire survey and interpreted into readable and informative data through Reliability Analysis, Descriptive Analysis and Pearson’s Correlation. The findings supported all three (3) objectives which mean there is relationship between all three (3) independent variables which are extrinsic rewards, job satisfaction and employee empowerment with the dependent variable, employee retention.